(untitled) (Heritage, 2023)
Children and minors in most criminal legislations in the world enjoy a privileged status due to their psychological and physical immaturity. While children belong to the category of completely criminally irresponsible persons, minors are subject to liability, but under specific conditions, defined by the Criminal Code of the Republic of Serbia and the Law on juvenile offenders and the criminal protection of minors. The latest events that have taken place in the Republic of Serbia have encouraged thinking about whether the age limit for criminal responsibility should be reduced, whether punitive measures should be tightened and what preventive measures should be taken to reduce the issue of children and minors committing crimes and prevent tragedies like the tragedy from happening again in the model elementary school "Vladislav Ribnikar" in Belgrade.